2011
DOI: 10.1038/nature10538
|View full text |Cite
|
Sign up to set email alerts
|

Motor antagonism exposed by spatial segregation and timing of neurogenesis

Abstract: Walking is a key motor behaviour of limbed animals, executed by contraction of functionally antagonistic muscle groups during swing and stance phases. Nevertheless, neuronal circuits regulating the activation of antagonistic extensor-flexor muscles remain poorly understood. Here we use monosynaptically restricted trans-synaptic viruses to elucidate premotor anatomical substrates for extensor-flexor control in mice. We observe a medio-lateral spatial segregation between extensor and flexor premotor interneurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
203
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(222 citation statements)
references
References 62 publications
15
203
4
Order By: Relevance
“…Current exciting research has revealed the ability of tuned circuits involving flexor-and extensor-based interneurons within the spinal cord involved in locomotion, and that proprioceptive input to these circuits may participate in regulating gait during motion (Tripodi et al, 2011). We observed no specific exercise-induced changes in proprioceptive sensation, but this may be irrelevant in the context of integration of proprioception in complex circuit function in locomotion.…”
Section: Discussionmentioning
confidence: 76%
“…Current exciting research has revealed the ability of tuned circuits involving flexor-and extensor-based interneurons within the spinal cord involved in locomotion, and that proprioceptive input to these circuits may participate in regulating gait during motion (Tripodi et al, 2011). We observed no specific exercise-induced changes in proprioceptive sensation, but this may be irrelevant in the context of integration of proprioception in complex circuit function in locomotion.…”
Section: Discussionmentioning
confidence: 76%
“…Whether or not the orientation of the progenitor divisions is instructive for cell fate determination in the vertebrate nervous system is still under debate 51 . Besides, a previous characterization of the local spinal cord circuitry revealed that interneurons participating in distinct premotor circuits differ by the timing of their neurogenesis 52 ARTICLE birth defects we observed are unknown but could thus have profound impact, which opens fascinating perspectives for future studies. Sema3B and other extracellular cues could therefore play complementary role to that reported for intrinsic polarity in the spindle orientation 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that spinal motor neurons whose cell bodies are misplaced due to cadherin signalling defects have aberrant dendritic arbors (Demireva et al 2011 ), and that blocking the Reelin signal results in abnormal dendritic morphologies (Senturk et al 2011 ;Rice et al 2001 ), it is plausible that cell body position could potentially impact how spinal motor neurons receive and integrate the signals normally passing through axon-dendritic synapses. Another recent fi nding that potentially impacts how we view motor neuron soma position, functional connectivity and dendritic arborisation is the observation that pre-motor interneurons that directly synapse onto spinal motor neurons are organised in a spatially segregated manner that mirrors that of motor neuron divisions (Tripodi et al 2011 ).…”
Section: Organisation Of Spinal Motor Neuronsmentioning
confidence: 99%